PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK BERBASIS ETNOMATEMATIKA DAN PRESTASI BELAJAR SISWA - Uskono, Irmina Veronika; Lakapu, Meryani; Jagom, Yohanes Ovaritus; Dosinaeng, Wilfridus Beda Nuba; Bria, Kornelis (Journal of Honai Math, 2020)
Buna is one of the woven motifs from Insana, East Nusa Tenggara Province that uses geometric motifs like a rhombus. Rhombus is a challenging material so students only memorize the formula without understanding the concept.Â Â In order to overcome this problem, a weaving learning based on ethnomathematics has been proposed. The purpose of this study is to understand the impact on the learning achievement of students of the implementation of a realistic mathematical approach based on ethnomathematics. This is a quantitative study using a one-group pretest-posttest design. The population for this study is all fifth-grade students of SDN Bestobe, Insana District. Pretest and posttest results obtained are used for the analysis. The statistical test used is a paired sample t-test. The results show that the implementation of realistic mathematical learning based on ethnomathematics has a substantial influence on the learning achievement of mathematics students. These results contribute to adding empirical evidence related to the relationship between Ethnomathematics-based Realistic Mathematics Education approaches to student achievement.